Analisis Ketimpangan Ekonomi Antarwilayah di Provinsi Jawa Tengah Sebelum Omnibus Law Cipta Kerja - Mahardhika Cipta Raharja; Unik Lestari (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2022)
This study analyzes the effect of Foreign Investment (PMA), Domestic Investment (PMDN), and the Human Development Index on the inequality of district/city development and how the mediating variable of the Human Development Index (IPM) also affects the inequality of district/city development in Central Java Province, before the Omnibus Law Cipta Kerja. Data analysis uses path analysis with the Eviews program, using data from 35 districts/cities in Central Java Province in the 2016-2019 period. The result is that PMDN and PMA have a positive effect on IPM. PMDN and IPM have a negative effect on development inequality, while PMA has no effect on district/city development inequality in Central Java Province.